Development of Music Intelligence in Paud Region of Surakarta Through the Angklung Game. - Paulus Widjanarko; Eka Titi Andaryani (Zien Journals, 2022)
Early Childhood Education (PAUD) is a basic education for a child. Through PAUD children can be thoroughly facilitated in terms of their growth and development. Of course, through PAUD, children can also get a stimulus or support for growth and development in the love of their homeland, namely through the development of musical intelligence. This is especially about the art of traditional music for children. In addition, children's talent for musical intelligence has also been indirectly stimulated. One example of traditional music is angklung. Angklung is a type of musical instrument that can provide a special attraction for children. When the child feels happy and interested, then the musical intelligence according to what is expected can increase through the music learning that has been given. Research using qualitative methods is the choice of the researcher. This research will be conducted in PAUD Surakarta area. Some of the considerations made by the researcher in choosing the area, one of which is because there are many PAUD institutions in Surakarta whose conditions and conditions are in accordance with the background of the problems that the researchers take. This is because there is a music center learning with angklung media. The technique that will be used in this research is to collect data first. Initially, it can be started by conducting questions and answers or interviews, then observing or observing directly to the selected institution. Then just do the documentation. Based on the results of the analysis and what has been discussed and described by the researchers, it can be concluded that the musical intelligence of PAUD children in the Surakarta area has mostly begun to develop, although it is still gradual. This can be seen in several indicators in the development of musical intelligence. Children are not able to harmonize. to the elements of musical intelligence itself. This is as in the harmony of sound, rhythm, pitch, accent, and volume. However, the children are still engrossed in the activities from start to finish that have been given. They look happy and don't seem bored
Keywords: Angklung; Music Intelligence; Playing; PAUD